Stargazing: Everyday lessons from coaching elite performers. - Kaiser, R. B. (Consulting Psychology Journal: Practice and Research, 2019)
As the capstone for a special issue of Consulting Psychology Journal: Practice and Research on coaching elite performers, this article provides a brief summary of differences and similarities across the 5 articles, which discuss coaching entrepreneurs and CEOs, Olympic athletes, performance artists, members of military special operations, and surgeons and emergency-room doctors. The essence of performance coaching is defined as helping individuals to increase their ability to perform under pressure. This is described as distinct from building and refining the physical or technical skills of one`s discipline and involves the development of psychological skills for self-management. A conceptual framework is provided for understanding and guiding this type of development with all types of clients—and not just elite performers—is provided, along with a summary of skills and techniques that coaches can teach their clients for increasing their capacity for peak performance.